The analysis of Caesarean Section Rate based on 10 groups Robson's Classification - Lorena Zijaj; Arian Shtylla; Jola Kerpaci; Irida Dajti (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Introduction: Caesarean Section use is growing in a progressive rate globally, accounting for 21% worldwide in 2012 up from 12% in 2000.The trend in Albania follow the same pattern with the overall rate rising steadily. Specifically, in "Koco Gliozheni" Hospital the rate went up from 29.5% in 2010 to 40.35% in 2017. The World Health Organization recommends the Robson Classification as an effective caesarean analysis and monitoring too.  Objective: The aim of this article is to evaluate the cesarean section rate of University Hospital of Obstetric-Gynecology "Koco Gliozheni".  Material and method: This is a retrospective cross sectional study conducted at obstetric department of Obstetric-Gynecology University Hospital "Koco Gliozheni" in Tirana from January 2016 to May 2017. All women admitted for childbirth were categorized into relative contribution made by each group.  Results: 1918 out of 4838 births were performed by caesarean section, which corresponds to a rate of 39.6 %. According to Robson classification the largest group was the group 5 (multiparous women at term, with a single cephalic presentation pregnancy) with a relative contribution of 31.6%. On second and third place were group 1(nulliparous women, at term with a single cephalic pregnancy, during spontaneous labor) and 2(nulliparous women at term,with single, cephalic presentation, who either had labor induced or CS before labor, especially the 2b subgroup with an elective CS) with relative contribution of 22.5% and 16.7% respectively. Groups 1;2;5 made an account of relative contribution of 76.2%. All other groups had altogether a relative contribution of 23.8% . Conclusions: In our study, Robson Groups 5(multiparous women at term, with a single cephalic presentation pregnancy), 1(nulliparous women, at term with a single cephalic pregnancy,during spontaneous labor), 2(nulliparous women at term,with single cephalic presentation,who either had labor induced or CS before labor) were identified as the main contributors to the overall CS rate at the University Hospital of Obstetric-Gynecology "Koco Gliozheni". It is important that efforts to reduce the overall CS rate should mainly be focused on the primary CS rate (group 1 and 2) and on increasing vaginal birth trail after CS (group 5).